2010
DOI: 10.1108/02686901011054854
|View full text |Cite
|
Sign up to set email alerts
|

Financial restatements and corporate governance among Malaysian listed companies

Abstract: Purpose-This paper seeks to examine the effects of Malaysian Code on Corporate Governance on the nature of financial restatements in Malaysia and whether corporate governance characteristics are associated with financial restatements. Design/methodology/approach-Data for this paper are obtained from annual reports that had been restated for the period of 2002-2005 with firm-years being the unit of observation. A control group comprising non-restating firms is formed using match-pair procedures where restated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(137 citation statements)
references
References 81 publications
(137 reference statements)
13
120
1
3
Order By: Relevance
“…Nevertheless, Apadore and Mohd-Noor (2013) have underlined that the more independent the board is the more problematic incentive it tends to be owing to the diversity of opinions that might well be brought about the auditing procedures and likely to impact further extend the audit span. This confirms by well the idea stipulating that the board independence does, by no means, not promote corporate transparency (Haniffa and Cooke, 2002; Wan-Hussin, 2009) nor does it entail any financial adjustments (Abdullah and al, 2010). Consequently, the below may well be posed: H3a: Outside director's proportion within the board negatively affects audit reporting quality.…”
Section: Outside Director's Proportion Within the Boardsupporting
confidence: 61%
“…Nevertheless, Apadore and Mohd-Noor (2013) have underlined that the more independent the board is the more problematic incentive it tends to be owing to the diversity of opinions that might well be brought about the auditing procedures and likely to impact further extend the audit span. This confirms by well the idea stipulating that the board independence does, by no means, not promote corporate transparency (Haniffa and Cooke, 2002; Wan-Hussin, 2009) nor does it entail any financial adjustments (Abdullah and al, 2010). Consequently, the below may well be posed: H3a: Outside director's proportion within the board negatively affects audit reporting quality.…”
Section: Outside Director's Proportion Within the Boardsupporting
confidence: 61%
“…This is consistent with Abdullah, Yusof, and Mohamad-Nor (2010) and Baatwah et al (2013) who anticipated an interaction between audit committee independence and expertise in ensuring audit committee effectiveness. It is widely known among authoritative bodies, practitioners and researchers that audit committee independence constitutes a crucial mechanism for ensuring the effective monitoring of audit committees (Blue Ribbon Committee (BRC) 1999; DeZoort et al 2002).…”
Section: Audit Committee Financial Expertisesupporting
confidence: 60%
“…Such directors might hinder the audit committee from performing its role effectively and raise the external auditor's concern about the internal control quality (Abdullah et al 2010). By using the pre revision sample, Abdullah (2006) and found that audit committee independence is not associated with timely audit report.…”
Section: Audit Committee Financial Expertisementioning
confidence: 99%
“…Based on their findings, [6], found an inconclusive evidence that the dominance of independent directors improves firms' financial performance. Similarly, [7] finding revealed that the presence of independent directors does not improve board monitoring in family owned companies While, [4] documented that independent directors reduce earnings ability to predict future cash flows in the Malaysian context. According to [8], the independent directors do not have an adequate understanding of the daily operation of the company.…”
Section: Introductionmentioning
confidence: 99%